Fungsi subandar dalam jaman Bali kuna, abad 9-10 Masehi - Wardha, I. Wayan (Fakultas Sastra, Universitas Udayana, 1984)
On the functions of a subandar or shahbandar, a bureaucratic institution, in Bali during the 9th to 10th century.